The Impact of Online Learning on The Motivation of University Level Preparatory EFL Students in Turkey - Yağmur, Başak (Technium Social Sciences Journal, 2022)
Online education or e-learning has been a part of education ever since required technological advancements came into existence. Online education’s efficiency and its impacts on both educators and learners have been questioned and investigated by many researchers and scholars since the COVID-19 global pandemic broke out. One of the many concerns is related to how online education affects learner motivation. Along with any educational setting or context, the role of online education and its effects on both learning and teaching processes has gained much interest and momentum in the context of EFL as well. In the early days of the pandemic, online education practically replaced traditional classroom settings and today, it continues to be an important part of learning English. For this reason, a good body of research and studies have focused on how online courses can affect the whole process of learning and teaching. This study aimed to investigate EFL learners’ views on online education and to investigate how online learning affected the motivation of EFL learners. A qualitative descriptive design was used, and data were collected with a close-ended questionnaire, to understand how students identify with online learning and how it affected their motivation. 118 English preparatory program students at a foundation university participated in the study. The study findings reported mixed results. According to the findings, a considerable percentage of students claimed their motivation was negatively affected, although some students considered online lessons effective for target language learning.